Educators’ perspectives on nurturing spirituality in faith-based early childhood education: A qualitative study - Nafisah, Aisyah Durrotun; Maronta, Yusuf; Putri, Nilamsari Kusumawati; Yuanhong, Luo; Rachman, Hanifa; Dhafet, Nur Aeni Muhlisa; Rozaan, Rifqizaqia (UIN Ar-Raniry Banda Aceh, 2025)
Early childhood educators, especially in faith-based institutions, need to have a deep understanding of children's spirituality in order to design and respond to spiritual experiences that arise spontaneously. This study aimed to explore the personal insights and experiences of educators regarding spirituality, as well as their understanding and approaches in fostering spirituality among young children. A qualitative research design was employed, guided by three key questions. The sample included nine educators from a faith-based early childhood program in Kudus, Central Java, specifically involved with 3 and 4-year-olds in class A, which consisted of three classes. Data collection techniques using observation, interviews, and documentation. Findings indicated that the personal insights and experiences of educators play a pivotal role in boosting children's spirituality. Consequently, there are significant opportunities to support educators in their own development and to provide relevant information regarding children's spirituality. Based on the findings, it is suggested that to effectively nurture children's spirituality, educators should cultivate their own sense of personal spirituality, which entails having experienced spiritual events in their own lives essentially spiritual formation. Additionally, educators must possess the knowledge and skills to reflect on their spirituality and effectively integrate these experiences with their early childhood teaching methodologies in order to create meaningful spiritual opportunities for children. The study recommends enhancing the competencies of educators in promoting the spirituality of young children. This research contributes valuable insights into the understanding of spirituality within religious-affiliated early childhood education settings.